Effects of Two Different Energy Sources in Total Mixed Diets on the Performances and Blood Metabolites of Lactating Boerka Goats - Simon Petrus Ginting; Andi Tarigan; Kiston Simanuhuruk; Antonius -; Solehudin - (Indonesian Center for Animal Research and Development (ICARD), 2020)
Lactating goats are prone to negative energy status due to increased body fat reserve mobilization to support the high energy requirement of milk production. The study was aimed to investigate the responses of the lactating goat on diets provided in total-mixed ration differing in the energy sources. The experiment was conducted using a total of 35 does having 2-3 parities and an average bodyweight of 30.3±4.48 kg and BCS of 2.5 ± 0.05 on a scale basis of 1 to 5. Animals were allocated to one of five dietary treatments (seven animals/treatment) formulated to be iso-nitrogen dan iso-calory in a total mixed ration. Cassava meal was used as the source of glucogenic energy and bergafat as the main source of lipogenic energy. There were no DM intake differences (P>0.05) between the glucogenic diet (1.49% and 2.28% fat), but significant increases (P